Theory of electron spin resonance in bulk topological insulators Bi2Se3, Bi2Te3 and Sb2Te3. (17th March 2016) - Ly, O; Basko, D M
Abstract: We report a theoretical study of electron spin resonance in bulk topological insulators, such as Bi2 Se3, Bi2 Te3 and Sb2 Te3 . Using the effective four-band model, we find the electron energy spectrum in a static magnetic field and determine the response to electric and magnetic dipole perturbations, represented by oscillating electric and magnetic fields perpendicular to the static field. We determine the associated selection rules and calculate the absorption spectra. This enables us to separate the effective orbital and spin degrees of freedom and to determine the effective g factors for electrons and holes.